Designing of Numeracy Questions for Middle School Level Students - Wulan Izzatul Himmah; Nurul Hidayah; Shafanafi Azzahra (Hipotenusa: Journal of Mathematical Society, 2024)
Numeracy is a skill that has begun to be paid attention to in recent years, including in Indonesia. When solving numeracy questions, students often find it difficult, especially if the stimuli used in the questions are unfamiliar to students. Teachers can bridge this by using numeracy questions starting with stimuli that the students are familiar with or are around the students. The aim of this research is to produce numeracy questions at the middle school level that are suitable for use. This research is Research and Development research with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The instruments used in this research were interview guides and questionnaires. Question validation was carried out by providing draft questions to 2 experts in the field of mathematics education at State Universities in Central Java, Indonesia. Data was analyzed descriptively, both qualitatively and quantitatively. The results of this research show that references to numeracy questions are needed. After preparing the numeracy questions through the design and development process, it was discovered that the questions prepared received a score of 4.27 in the very good category from expert validators.